2013
DOI: 10.3917/parti.006.0005
|View full text |Cite
|
Sign up to set email alerts
|

Gouvernementalité et participation

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 61 publications
0
6
0
2
Order By: Relevance
“…These studies have shown how participatory projects construct their participants' subjectivities in specific ways in order to meet the projects' varied objectives (e.g. Gourgues, Rui, and Topçu 2013;Charles 2016, loc. 19; Barnes, Newman, and Sullivan 2007, 63-70;Newman and Clarke 2009, 138-139).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown how participatory projects construct their participants' subjectivities in specific ways in order to meet the projects' varied objectives (e.g. Gourgues, Rui, and Topçu 2013;Charles 2016, loc. 19; Barnes, Newman, and Sullivan 2007, 63-70;Newman and Clarke 2009, 138-139).…”
Section: Introductionmentioning
confidence: 99%
“…Charles 2016; Newman and Tonkens 2011) and on the diverse objectives set for the projects, as well as the rationales underpinning them (Ganuza, Baiocchi, and Summers 2016;Dagnino 2007; Barnes, Newman, and Sullivan 2007;Gourgues, Rui, and Topçu 2013). Thus far, less attention has been paid to how the initiatives work on their participants' subjectivities -techniques that Kim McKee (2009, 478) calls 'the micropractices of local initiatives'.…”
mentioning
confidence: 99%
“…Inspired by Foucault's approach (1982), many authors in both literatures demonstrate that participatory arenas are sites where power relationships are reproduced and entrenched through control of the bodies and discourses of participants, with the establishment of norms defining prescribed behaviours in those spaces (Gourgues and al., 2013; Kothari, 2001). Those in charge of setting up participatory arenas, either development practitioners and/or officials representing the state, define the norms.…”
Section: Participatory Development and Power: Challenge Or Entrenchment?mentioning
confidence: 99%
“…Those in charge of setting up participatory arenas, either development practitioners and/or officials representing the state, define the norms. Gourgues and colleagues (2013) argue that participation aims to reduce conflict and divert citizens’ attention away from their grievances. When citizens are kept busy with participation, they are prevented from contesting social exclusion (Jouve, 2005; Palomares and Rabaud, 2006).…”
Section: Participatory Development and Power: Challenge Or Entrenchment?mentioning
confidence: 99%
“…L'analyse de Goldschmidt et Garnier démystifie les pseudo velléités émancipatoires qui présideraient à ce « virage à gauche », en expliquant qu'il s'agit avant tout d'une nécessité historique de pacification des rapports sociaux liée à la crise économique qui a conduit à cette stratégie pour focaliser l'attention et capter la participation au niveau local, désolidarisant ainsi les classes populaires et décentrant le discours revendicatif. La politique locale et participative existe encore aujourd'hui, des conseils de la vie locale aux désormais célèbres grands débats publics66 , et continue de proposer des modèles consultatifs évitant toute conflictualité exprimant les antagonismes sociaux. La stratégie localiste et participative s'est étendue dans différents champs.…”
unclassified